(untitled) (Eurasian Journal of Ecology, 2018)
Wheat (Triticum aestivum L.) is grown in many countries around the world, its productivity is hampered due to a variety of abiotic stresses such as drought, salinity, and heat, particularly in arid and semiarid regions of the world. Of these, drought as complicated factor, is the major abiotic stress that is regarded as highly deleterious to growth and productivity of the wheat. Drought inhibits a variety of physiological processes in plants. Drought continues to be an important challenge to agricultural researchers and plant breeders. Drought is a major abiotic factor limiting the crops yield grown more than one third of the arable land around the world. Polyamines are endogenous plant growth promoters that affect a variety of physiological and metabolic functions, and they particularly involved in the flowering process. Studies conducted with other crop plants indicated that there is relationship between changes in polyamine content and drought tolerance. However, no information exists regarding to polyamine content of wheat under conditions of limited water supply. This study was aimed quantifying the effect of drought on different classes of polyamine such as putrescine, spermidine and spermine concentrationin the parent line Zhenis and M7mutant lines developed on its genetic basis using gamma radiation doses of 100 and 200 Gy resulting changes in their concentrations. The article presents screening parent variety of spring wheat Zhenis and M7 mutant lines developed on its genetic basis using gamma radiation doses of 100 and 200 Gy on polyamine content in plants grown under watered and drought condition. The wheat mutant germplasm, grown under irrigation had 4 samples, which are characterized by significantly increase in polyamines concentration. On the genetic basis of varieties Zhenis gamma radiation dose of 100 Gy on the basis of putrescine concentration have been identified two significant positive mutant linesunder drought conditions. Key words: drought, polyamines, putrescine, spermidine, spermine, wheat, mutant lines.